Energy management, supply and conservation - Beggs, Clive (Oxford : Butterworth-Heinemann, 2002)
With more and more concern being expressed over the Earth's dwindling energy resources as well as rising pollution levels, the subject of energy management and conservation is becoming increasingly important. Over half of all energy consumed is used in buildings so effective management of buildings whether commercial or domestic is vital. This book is a comprehensive text dealing with the theory and practice of the supply of energy to consumers, energy management and auditing and energy saving technology. It will be a core text on courses on energy management and building services, as well as updating professionals in the building sector. * Comprehensive text dealing with in depth coverage of energy supply as well as energy use and conservation * Practical advice on implementation of energy-saving technologies and assessment methods.
Energy management in context; The utility companies and energy supply; Competition in energy supply; Energy auditing; Energy analysis techniques; Energy economics; Energy monitoring and targeting; Energy efficient heating; Waste heat recovery; Combined heat and power (CHP); Energy efficient air conditioning and refrigeration; Electrical services and lighting; Passive environmental control in buildings.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Energy conservation; Energy consumption; Buildings -- Energy conservation; Buildings -- Energy consumption; Electronic books